Regulations and Brain Drain: Evidence from Wall Street Star Analysts’ Career Choices - Guan, Yuyan; Li, Congcong; Lu, Hai; Wong, M. H. Franco (Management Science, 2019)
The Global Settlement, along with related regulations in the early 2000s, prohibits the use of investment banking revenue to fund equity research and compensate equity analysts. We find that all-star analysts from investment banks are more likely to exit the profession or move to the buy side after the regulations. The departed star analysts’ earnings revisions and stock recommendations are more informative than those of the remaining analysts who followed the same companies. To the extent that star analysts are superior to their nonstar counterparts in terms of research ability and ability to inform the market, the exit of star analysts represents a brain drain in the sell-side equity research industry. These results are consistent with the view that the regulations introduced to protect equity investors have unintended adverse effects on the investors due to a brain drain in investment banks. This paper was accepted by Suraj Srinivasan, accounting.